Factors Influencing Delay in Construction/Civil Engineering Projects in the Persian Gulf Countries - Alavi Toussi, Maryam; Whyte, Andrew (Research Publishing Services, 2012)
A large number of projects around the world experience extensive delays; that is to say they go beyond initial time and cost estimates. There are various causes of delay in different countries including social, economical, political, environmental and religious issues. Severe weather conditions, heavy rains and floods are the most important causes of delay in road construction projects in Central Africa; on the other hand, in the Middle East, many delays are due to ineffective planning, shortage of labour and workmanship, whilst in West Central Asia many constructional delays are caused by changing orders and owners financial constraints. The work presented here discusses the extent to which geographical location and socio-economic variables affect construction delay generally, and examines in particular the main reasons of delay (and a means to address and mitigate such delay) in construction projects in the Persian Gulf. The work explores key factors of delay related to reliance of construction budget(s) upon oil price in locations where 85% of the national construction and infrastructure budget is derived from the oil income, and where fluctuations in dollar-per-barrel costs have a knock-on effect for construction project interim payments and final accounting to allow practical completion; discussion is made (in this early-stage research-project discussion paper) of an accurate means to predict and then allocate risk and fluctuation allowances into both the pre-contract feasibility stage as well as on-site activities directed and controlled by contractual arrangement.